Giáo trình thực hành tiếng nâng cao II :Dành cho sinh viên nước ngoài /Vũ Thị Ngọc Dung, Nguyễn Hải Quỳnh Anh, Nguyễn Thị Hồng, Nguyễn Hồng Lê. - Nguyễn, Thị Hồng.
Sách chương trình cử nhân Việt Nam học.